Young Social Entrepreneurship: The KKN Program Leading them to be one? - Khwarazmita, Tsabita; Sudiyono, Widhiyo (Journal of Career and Entrepreneurship, 2024)
This study investigates the impact of community service programs (KKN) on management and business student’s career choices as social entrepreneurs. Social entrepreneurship emphasizes sustainability and solving social problems, requiring innovative and practical approaches. The research focuses on understanding how KKN experiences influence students’ decisions to pursue social entrepreneurship careers. The methodology is narrative-based, with interviews conducted to gather in-depth participant insights. Five students who participated in KKN were selected, and their stories were analyzed to identify common themes related to social entrepreneurship. Results reveal that KKN experiences impact students’ career choices by exposing them to real-world social issues and enabling them to apply academic knowledge in practical settings. The study finds that students develop strong motivations to pursue social entrepreneurship careers through KKN, driven by their desire to solve community problems and contribute positively to society. The narratives highlight critical themes of well-being and sustainability, showcasing the transformation effect of KKN on students’ career aspirations. In conclusion, the research underscores the importance of integrating social entrepreneurship into higher education curricula, mainly through community service programs, to foster future social entrepreneurs capable of addressing societal challenges effectively.